2000
DOI: 10.1021/jf0009347
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Endothelium-Dependent Vasorelaxing Compounds from Grape Seeds

Abstract: Previous work has shown that red wines, grape juices, and other grape products cause endothelium-dependent relaxation (EDR) of blood vessels in vitro by increasing nitric oxide production. In this paper we describe the isolation and characterization of some of the compounds responsible for EDR activity. Concord grape seeds were extracted with methanol and the compounds were separated by Toyopearl TSK HW-40S chromatography. Resulting fractions (primarily phenolic acids, catechins, and proanthocyanidins) were fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
68
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 23 publications
5
68
0
Order By: Relevance
“…The urinary yield of anthocyanins was reported as 0.036± 0.043% of the ingested dose after consumption of a blackcurrant juice similar to that consumed in this study (Hollands et al, 2008). Vasodilatory effects of cyanidin-3-glucoside, and delphinidin glycoside-rich and cyanidin glycoside-rich juices have been reported but only at higher levels of intake (Stein et al, 1999;Fitzpatrick et al, 2000;Xu et al, 2004;George et al, 2009).…”
Section: Discussionsupporting
confidence: 66%
“…The urinary yield of anthocyanins was reported as 0.036± 0.043% of the ingested dose after consumption of a blackcurrant juice similar to that consumed in this study (Hollands et al, 2008). Vasodilatory effects of cyanidin-3-glucoside, and delphinidin glycoside-rich and cyanidin glycoside-rich juices have been reported but only at higher levels of intake (Stein et al, 1999;Fitzpatrick et al, 2000;Xu et al, 2004;George et al, 2009).…”
Section: Discussionsupporting
confidence: 66%
“…The present findings that resveratrol inhibited the CA secretory responses evoked by both nicotinic receptor stimulation as well as by membrane depolarization from the rat adrenal medulla also seem to support the fact that, in in vivo studies, PCRW lowers blood pressure in normotensive and hypertensive rats (Mizutani et al, 1999;Diebolt et al, 2001). It has been reported that red wines and grapes exhibit endothelium-dependent relaxation of blood vessels via enhanced generation and/or increased biological activity of NO, leading to the elevation of cGMP levels (Fitzpatrick et al, 1993;Fitzpatrick et al, 1995;Fitzpatrick et al, 2000;Zenebe et al, 2003). Therefore, these experimental results indicate that resveratrol-induced inhibitory activity of CA secretory response evoked by stimulation of nicotinic receptors may contribute at least partly to its hypotensive mechanism.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, through bioassay-guided fractionation of crude GSE using the rat aortic vasorelaxation model, increasing EDR activity was demonstrated to correlate with increased concentrations of procyanidin oligomerization [56,57]. This finding suggests that highly polymerized polyphenols (Figure 1f), although not studied extensively in other botanicals, may play a significant role in the hypotensive activities of GSEs [56,57].…”
Section: Grape Seed: Vitis Vinifera L (Vitaceae)mentioning
confidence: 99%
“…Several in vitro studies have demonstrated endothelium-dependent relaxation (EDR) as the primary mechanism of action for GSE [55][56][57]. Interestingly, through bioassay-guided fractionation of crude GSE using the rat aortic vasorelaxation model, increasing EDR activity was demonstrated to correlate with increased concentrations of procyanidin oligomerization [56,57].…”
Section: Grape Seed: Vitis Vinifera L (Vitaceae)mentioning
confidence: 99%